Review of recent advances in piezoelectric material for nanogenerator application: Preparation methods, material selection, performance, applications, and future outlook - Nurul Syafiqah Mohamed Mustakim; Dayana Kamaruzaman; Mohd Hanapiah Abdullah; Mohd Firdaus Malek; Norfarariyanti Parimon; Mohd Khairul Ahmad; Suriani Abu Bakar; Nagamalai Vasimalai; Seeram Ramakrishna; Mohamad Hafiz Mamat (Springer US, 2024)
Extensive research has focused on green and renewable energies to address the increasing demand for flexible, reliable, and self-sustaining advanced technology and electrical supplies. Piezoelectric nanogenerators (PENGs) have garnered significant interest as a pioneering energy-harvesting technology, due to their notable advancements and capacity to effectively capture and convert mechanical energy from the environment into electrical power. This review article seeks to cover the latest developments and innovations in piezoelectric materials for PENG applications. It explores key topics, such as the strategic selection of piezoelectric materials to optimize energy-harvesting efficiency, advancements in fabrication techniques, and the evaluation of PENGs performance. Throughout this manuscript, critical points are highlighted that require further investigation in the field of high-performance piezoelectric material fabrication. Ongoing research is crucial for improving the flexibility and durability of functional materials, thus advancing the development of superior electronic devices with enhanced piezoelectric properties. Furthermore, addressing enhancements in the electromechanical properties of current piezoelectric materials is imperative. This review article aims to support researchers in their quest for a comprehensive understanding of piezoelectric mechanisms and offers valuable insights for the progression and refinement of PENGs, which have broad potential applications.